International Reserves and Foreign Currency Liquidity : Guidelines for a Data Template. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2014)
This book is an update of the Guidelines published in 2001. It sets forth the underlying framework for the Reserves Data Template, and provides operational advice for its use. The updated version also includes three new appendices aimed at assisting member countries in reporting the required data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet